The Association Between Personality Traits and Psychiatric Disorders: A Comparative Study of Violent and Non-Violent Offenders in a Nigerian Correctional Centre - Ifedayo Ajayi (BJPsych Open)
Aims: The study examined and compared the association between personality traits and psychiatric disorders among violent and non-violent offenders in a correctional centre in Nigeria.